(untitled) (Proceedings of Southern Federal University. Philology, 2020)
One of pressing problems of modern Russian studies is the study of epistolary appealing to power by Russian writers. These appeals, along with a friendly letters, are rightfully singled out in special genre. Letters by A.S.Pushkin’s pen include appeals to emperors – Alexander I and Nicholas I; M.A.Dondukov-Korsakov and S.S.Uvarov; correspondence by Pushkin and A.H.Benckendorf deserves separate analysis. We analyze thematic range of these appeals (relationship between the poet and the authorities; the poet’s ill health; his work, relationship with censorship and even personal life). Key words: «letter to ruler», «letter to Tsar», epistolary genre, A.S.Pushkin, Russian literature of the XIX century. DOI 10.18522/1995-0640-2020-3-112-119